In the womb - Macdonald, Toby.; Greening, Andy.; National Geographic Channel (Television station : Washington, D.C.) ([Washington, D.C.] : National Geographic Channel, 2005)
Uses photography, computer graphics and 4-D imaging to show the development of a female human fetus from conception to birth.
Taped off-air with permission on March 11, 2005.
DVD.
Keywords: Fetus -- Growth; Childbirth